2017
DOI: 10.1016/j.jpain.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Factors Associated With Pain in Older Homeless Individuals: Results From the Health Outcomes in People Experiencing Homelessness in Older Middle Age (HOPE HOME) Study

Abstract: Individuals experiencing homelessness in the United States are aging; little is known about chronic pain in this population. In a cross-sectional, population-based study, we interviewed 350 homeless individuals aged 50 and older to describe pain experienced by older persons experiencing homelessness and to assess factors associated with chronic moderate to severe pain, defined as pain lasting ≥3 months, with a past week average severity score of 5–10 (scale 0–10). The median age of participants was 58 years. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 89 publications
0
26
1
2
Order By: Relevance
“…Consistent with results of previous studies among homeless people, we found that older age was associated with worse physical health (Abdul‐Hamid, ; Brown & Steinman, ; Garibaldi et al, ; Gelberg et al, ; Kellogg & Horn, ; Kimbler et al, ; Nakonezny & Ojeda, ; Tompsett et al, ) and that about 30 percent of both the older and younger homeless people had elevated levels of psychological distress (DeMallie et al, ; Garibaldi et al, ) and were screened positive for suspected intellectual disability (Hurstak et al, ; Spence, Stevens, & Parks, ). Among both older and younger homeless people in our study, levels of substance use were lower than generally reported in studies among homeless populations (DeMallie et al, ; Garibaldi et al, ; Landefeld et al, ; Nielsen et al, ; Tompsett et al, ). As many as 33.0% and 27.8% of the older participants, compared to 19.6% and 14.6% of the younger participants in our study reported to only rarely or never receive social support from family and friends or acquaintances, respectively.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Consistent with results of previous studies among homeless people, we found that older age was associated with worse physical health (Abdul‐Hamid, ; Brown & Steinman, ; Garibaldi et al, ; Gelberg et al, ; Kellogg & Horn, ; Kimbler et al, ; Nakonezny & Ojeda, ; Tompsett et al, ) and that about 30 percent of both the older and younger homeless people had elevated levels of psychological distress (DeMallie et al, ; Garibaldi et al, ) and were screened positive for suspected intellectual disability (Hurstak et al, ; Spence, Stevens, & Parks, ). Among both older and younger homeless people in our study, levels of substance use were lower than generally reported in studies among homeless populations (DeMallie et al, ; Garibaldi et al, ; Landefeld et al, ; Nielsen et al, ; Tompsett et al, ). As many as 33.0% and 27.8% of the older participants, compared to 19.6% and 14.6% of the younger participants in our study reported to only rarely or never receive social support from family and friends or acquaintances, respectively.…”
Section: Discussioncontrasting
confidence: 68%
“…These findings suggest that differences between older and younger homeless people might also be present for other clinically relevant health outcomes. Nevertheless, only few studies have specifically examined health‐related characteristics of older homeless people (Brown et al, ; Brown, Kiely, Bharel, & Mitchell, ; Landefeld et al, ) or investigated health differences between older and younger homeless people (Abdul‐Hamid, ; Brown, Kimes, Guzman, & Kushel, ; Brown & Steinman, ; DeMallie, North, & Smith, ; Garibaldi, Conde‐Martel, & O'Toole, ; Gelberg, Linn, & Mayer‐Oakes, ; Hategan, Tisi, Abdurrahman, & Bourgeois, ; Kellogg & Horn, ; Kimbler, DeWees, & Harris, ; Nakonezny & Ojeda, ; Tompsett, Fowler, & Toro, ). The studies that have made such age comparisons consistently reported poorer physical health among older than younger homeless adults, but yielded conflicting results with regard to mental and psychosocial health, substance use, healthcare service use and health‐related needs (Abdul‐Hamid, ; Brown et al, ; Brown & Steinman, ; DeMallie et al, ; Garibaldi et al, ; Gelberg et al, ; Hategan et al, ; Kellogg & Horn, ; Kimbler et al, ; Nakonezny & Ojeda, ; Tompsett et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Covariates included sociodemographic and clinical variables shown to be associated with overdose in prior studies: age, race, psychological distress, current homelessness, and medical comorbidities. [22][23][24] We also included variables associated with homelessness and adverse health outcomes that we hypothesized would be associated with overdose in individuals experiencing homelessness: severe chronic pain 25,26 and social support. 27,28 The multivariable analyses excluded individuals with missing data on 1 or more study variables.…”
Section: Discussionmentioning
confidence: 99%
“…Due to socioeconomic factors, treating chronic pain and depressive symptoms may be challenging in a low income, racially and ethnically diverse patients [13,14]. Disparities in access to prescription and non-prescription treatment for chronic pain and associated conditions may contribute to negative impact on economic (ability to work), emotional (social isolation), and daily functioning [1517]. For example, minority patients with chronic pain receive less patient education, medications, surgery, and specialty referrals [14].…”
Section: Introductionmentioning
confidence: 99%
“…For example, minority patients with chronic pain receive less patient education, medications, surgery, and specialty referrals [14]. Access to non-pharmacological therapies is challenging as these therapies are often located far from low income neighborhoods, require an out of pocket payment, may not be covered by health insurance, and are less likely to be offered as a treatment to low-income or under-represented minority patients [1823].…”
Section: Introductionmentioning
confidence: 99%